Evaluation of Traffic Performance due to Closing Access to Private Vehicles on Pintu Besar Selatan Street for Mass Transportation (Case Study: Pancoran Street, West Jakarta Administrative City) - Azhari, Fadhilla; Arifin, Zaenal; Isradi, Dr. Muhammad (Recent Trends in Civil Engineering and Built Environment, 2025)
To expand the implementation of a Low Emission Zone (LEZ) in the Kota Tua area by restricting vehicles passing on Pintu Besar Selatan Street to only Transjakarta buses and diverting private vehicles to Pancoran Street, which is a commercial area and there is parking on the road which hinders the smooth flow of traffic. This study aims to analyze the effect of traffic performance on Pancoran Street due to the diversion of private vehicles from Pintu Besar Selatan Street in the planning year and alternative solution and parking characteristics on Pancoran Street. This research focuses on the evaluation of road performance and analysis of parking characteristics using Indonesian Road Capacity Guidelines (PKJI 2023), PTV Vissim, and Parking Facility Planning and Operation Guidelines 1998. Based on the analysis in the alternative problem solving for the planning year 2029, the implementation of odd-even and off-street parking has an effect on traffic performance, which has improved significantly by reducing the level of service (LOS) value was originally D for Pancoran Street Lane I and Lane II to C in Lane I and B in Lane II, reducing the average delay from 2,03 seconds originally to 1,95 seconds and increasing the network speed from 15,89 km/hour originally to 34,33 km/hour. The results of the parking analysis show that the parking space requirement is 18 SRP at the 00-corner parking and 29 SRP at the 600-corner parking, which means that the land is still able to accommodate, furthermore the parking changes often hinder the smooth flow of traffic. The recommendation that can be given is that it is necessary to implement alternative solutions to improve city traffic immediately and it can reduce air quality problems.